Medical students' perceptions of small group teaching effectiveness in hybrid curriculum - Pradeep Kumar Sahu; Shivananda Nayak; Vincent Rodrigues (Wolters Kluwer Medknow Publications, 2018)
Objectives: The objective of this study was designed to investigate medical students' perceptions of small group teaching effectiveness in a hybrid curriculum. Materials and Methods: A cross-sectional, descriptive survey was conducted at the School of Medicine, The University of the West Indies, St. Augustine where we collected the data from 195 undergraduate students. A self-administered questionnaire consisting of 25 items was used to measure students' perception on the effectiveness of problem-based learning (PBL) with regard to learning experience, teamwork, confidence, communication skills, and role of the tutor. Statistical analyses included mean and standard deviation for the description of each item; t-test to compare the mean scores for gender and class year, and one-way analysis of variance between groups for age group comparisons. Results: The students overall perceptions of small group teaching effectiveness showed that the PBL sessions were beneficial to their learning process (mean: 3.63 ± 0.46). Students have positive perceptions toward small group effectiveness, particularly in learning experience (mean: 3.98 ± 0.63) and teamwork (mean: 3.67 ± 0.58). The mean scores, measuring teamwork, for 2nd year students was significantly higher than that for 1st year students (3.76 ± 0.55 and 3.55 ± 0.60 respectively, P = 013). A similar significant trend was observed between 2nd year and 1st year students on communication skills (3.48 ± 0.67 and 3.29 ± 0.55, respectively, P = 0.046). Conclusions: PBL is an effective small group teaching method for medical students. Faculty development and students' training programs are required before implementing PBL.